2022
DOI: 10.1371/journal.pone.0263453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of photobiomodulation therapy and the intralesional administration of corticoid in the preoperative and postoperative periods of keloid surgery: A randomized, controlled, double-blind trial protocol study

Abstract: Keloid scars are characterized by the excessive proliferation of fibroblasts and an imbalance between the production and degradation of collagen, leading to its buildup in the dermis. There is no “gold standard” treatment for this condition, and the recurrence is frequent after surgical procedures removal. In vitro studies have demonstrated that photobiomodulation (PBM) using the blue wavelength reduces the proliferation speed and the number of fibroblasts as well as the expression of TGF-β. There are no proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In the process of skin healing, fibroblasts proliferate excessively and secrete a large amount of extracellular matrix, and cell apoptosis is delayed and degradation is insufficient, and local microvascular formation is increased, many factors promote its gradual formation of keloid [ 17 , 18 ]. 32 P released β-rays can directly or indirectly ionize and destroy DNA molecular structure, inhibit cell division and proliferation, inhibit fibroblast migration, proliferation and collagen synthesis and secretion, weaken immune cell function and reduce dysfunctional blood vessels, strongly inhibit inflammatory reaction, and can also effectively induce cell apoptosis and reduce TGF-β [ 19 ], Reduce the synthesis of extracellular matrix and collagen fiber, thus inhibiting the formation of keloid.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of skin healing, fibroblasts proliferate excessively and secrete a large amount of extracellular matrix, and cell apoptosis is delayed and degradation is insufficient, and local microvascular formation is increased, many factors promote its gradual formation of keloid [ 17 , 18 ]. 32 P released β-rays can directly or indirectly ionize and destroy DNA molecular structure, inhibit cell division and proliferation, inhibit fibroblast migration, proliferation and collagen synthesis and secretion, weaken immune cell function and reduce dysfunctional blood vessels, strongly inhibit inflammatory reaction, and can also effectively induce cell apoptosis and reduce TGF-β [ 19 ], Reduce the synthesis of extracellular matrix and collagen fiber, thus inhibiting the formation of keloid.…”
Section: Discussionmentioning
confidence: 99%
“…NIR (near infra-red) treatments have been noted to increase Cytochrome c oxidase activity, especially in the 10 Hz pulsed group, and transiently increase ATP and reactive oxygen species by disrupting the electron transport chain within the mitochondria (25). Besides wound healing, the effects of PBM on collagen synthesis and turnover could be utilized for other treatments such as hereditary gingival fibromatosis or keloid formation and hypertrophic scars (60)(61)(62)(63). Moreover, there has been tremendous recent progress on the evidence supporting PBM treatments in oncotherapy-associated oral mucositis (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Blue light, in particular, is reported to have an inhibitory effect on fibroblasts and TGF-β when administered at a higher energy density (up to 640 J/cm2). 211 Some studies have actually reported the benefits of PBM in the progress of postoperative healing of scars from different types of interventions, demonstrating the safety and efficacy of such therapy.…”
Section: Application Of Photobiomodulation In Keloid Managementmentioning
confidence: 99%
“…To be monitored in this sense will be the progress of the study proposed by Jefferson André Piresi et al entitled "Effect of the combination of PBM therapy and the intralesional administration of corticoid in the preoperative and postoperative periods of keloid surgery: A randomized, controlled, double-blind trial protocol study" whose prospectus was published on PLoS ONE on February 15, 2022 and registered on ClinicalTrials.gov (ID: NCT04824612). 211 The purpose of that study is to fill the absence of randomized double-blind trials on the subject of preventing keloid formation through the use of PBM. Specifically, the study was designed with a study group composed of 29 patients to whom PBM will be applied combined with the administration of intralesional corticosteroids in the preoperative phase and then, after surgical removal of the keloid, the PBM alone in the post-operative period using a blue LED light (470 nm, 400 mW, 4J per point on 10 linear points).…”
Section: Application Of Photobiomodulation In Keloid Managementmentioning
confidence: 99%